High-Energy Impact Behaviors of Hybrid Composite Plates Strengthened with 3D-UHMWPE Composites - Sang-Youl Lee; Gyu-Dong Kim; Sung Jig Kim; Chun-Ho Chang (Shock and Vibration)
This study deals with drop-impact effects of new hybrid concrete plates strengthened with an ultrahigh molecular weight polyethylene (UHMWPE). The proposed 3D-UHMWPE results in excellent mechanical properties such as high abrasion resistance, impact strength, and low coefficient of friction. These special properties allow the product to be used in several high-performance applications. In this study, we used two kinds of high-performance materials for the impact reinforcement of a structure made of conventional materials such as a concrete. In particular, the impact mechanism of a fiber-concrete hybrid structure was studied using various parameters. The parametric studies are focused on the various effects of drop-impact on the structural performance. The combined effects of using different fiber-reinforced materials on the impact behavers are also investigated.